Evaluating the Impact of Self-Directed PMM Digital Training Platform on Teacher Professional Competencies Using the Kirkpatrick Evaluation Model - Suharry; Fahmi Rizal; M. Giatman; Syaiful Haq; Lasyatta Syaifullah (Postgraduate, University of Mataram, 2025)
Civil servant teachers at SMK Negeri 2 Sungai Penuh face challenges in applying Platform Merdeka Mengajar (PMM) self-directed training results to classroom practices. This study evaluated the effectiveness of the PMM self-directed training program using the Kirkpatrick evaluation model. An evaluative research design was employed involving 20 civil servant teachers selected through purposive sampling. Data were collected using questionnaires, interviews, observations, tests, and documentation, then analyzed using SPSS Statistics Version 29 for descriptive and inferential statistics (paired t-test, effect size), and thematic analysis. Results demonstrated program effectiveness across all four Kirkpatrick levels. At the reaction level, teachers showed high satisfaction (M = 3.65-4.20). The learning level revealed significant competency improvements with paired t-test results (t = -24.367, p < 0.001) and exceptionally large effect size (Cohen's d = -5.449). At the behavior level, positive teaching behavior changes emerged (M = 3.85-4.00) across four competency dimensions. The results level identified transformative impacts including improved student learning outcomes, innovative methodologies (flipped classroom, gamification), efficient resource utilization, and optimized curriculum achievement. In conclusion, the PMM self-directed training program effectively improved teacher competency and transformed teaching practices at SMK Negeri 2 Sungai Penuh.